Pengembangan Minuman Fungsional Teh Bunga Krisan (Chrysanthemum morifolium ramat) dengan Penambahan Sari Kurma (Phoenix dactylifera L): The Development of Functional Drinks of Chrysanthemun Flower Tea (Chrysanthemum morifolium ramat) with the Addition of Date Palm Extract (Phoenix dactylifera L) - Siti Nurhalimah; Muhammad Rifqi; Regina Anggie Susilo (Universitas Djuanda, 2026)
Chrysanthemum tea is a functional beverage high in polyphenols, but it has shortcomings in sensory characteristics, particularly astringency. This study aims to determine the effect of brewing time and the addition of date juice to chrysanthemum tea drink. The study design used a factorial completely randomized design with brewing time treatments (5, 10, and 15 minutes) and date concentrations (15%, 30% and 45%). The results showed that brewing time and the addition of date juice affected polyphenol levels and several sensory parameters. Polyphenol levels fluctuated during the brewing time treatment but increased with increasing date juice concentration. Sensorially, color and density parameters were influenced by both factors, whereas neither factor affected aroma or taste parameters. The selected product has a 5-minute brewing time and the addition of 45% date extract (A1B3), with a polyphenol content of 1119 mg/kg, an inhibition percentage (antioxidant) of 87.58%, a pH of 5.8, and a total soluble solids of 9.25°Brix. The results showed that adding date extract increased polyphenol content and improved sensory characteristics, suggesting that chrysanthemum flower tea with date extract has the potential to become a functional drink acceptable to consumers.